The Epidemiology of Oral Carcinogenesis in the Indonesian Archipelago: A Cross-Sectional, Population-Based Analysis of Oral Cancer and Potentially Malignant Disorders Driven by Kretek Smoking and Betel Quid Chewing - Mariana Alifah; Sudarto Sudarto; Khalil Jibran; Theresia Putri Sinaga; Lisye Tiur Simanjuntak; Priscilla Kapoor (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Indonesia faces a severe but poorly quantified epidemic of oral cancer (OC) and oral potentially malignant disorders (OPMDs), driven by culturally endemic habits of kretek (clove cigarette) smoking and betel quid chewing. The absence of robust, large-scale epidemiological data has critically hampered the development of targeted public health interventions. This study aimed to determine the prevalence of OC and OPMDs and to quantify their association with these specific cultural practices in a large, geographically diverse Indonesian population. Methods: A multi-center, cross-sectional study was conducted across the Indonesian archipelago, enrolling 17,850 adults aged ≥30 years through a stratified, multi-stage cluster sampling design at community primary health centers (Puskesmas). Participants completed a structured questionnaire and underwent a standardized oral examination by calibrated dental professionals. All statistical analyses, including bivariate tests and multivariable logistic regression, were performed using survey-specific methods to account for the complex sampling design (stratification, clustering, and weighting) to produce nationally representative estimates. Results: The overall, nationally-weighted prevalence of the combined OC/OPMD outcome was 5.7% (95% CI: 5.2% - 6.2%). The prevalence was 4.9% for OPMDs and 0.8% for OC. After adjusting for confounders in a survey-weighted multivariable logistic regression model, current kretek smoking (Adjusted Odds Ratio [AOR]: 6.15; 95% CI: 4.98 - 7.59) and current betel quid chewing (AOR: 9.22; 95% CI: 7.31 - 11.63) were the most powerful factors associated with the presence of OC/OPMDs. A significant, non-linear dose-response relationship was observed for both habits. Conclusion: The burden of oral cancer and its precursors in Indonesia is substantial and is overwhelmingly associated with the culturally embedded habits of kretek smoking and betel quid chewing. These findings provide definitive, population-level evidence underscoring the urgent necessity for culturally-tailored public health strategies focused on cessation, regulation, and systematic early detection to mitigate this preventable cancer epidemic.